Effectiveness of Digital Application-Based Foot Care Education and Training Programmes in Improving Self-Efficacy and Foot Care Behaviour in Patients with Type 2 Diabetes Mellitus - Feriadianto Feriadianto; Dhea Natashia; Dewi Gayatri; Wati Jumaiyah; Winda Yuniarsih (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Type 2 diabetic mellitus with low self-efficacy, which affects how they take care of their feet. This can lead to reduced foot sensitivity and increase the risk of serious complications like ulcers and infections. Objective: To determine the effectiveness of of the Diabetic Educare digital application foot care education and exercise program on self-efficacy, foot care behaviour and foot sensitivity in patients with type 2 diabetic mellitus. Methods: Quasy experiment research design with two groups, namely the intervention group (n=27) and the control group (n=27). Data collection was using Diabetic Management Self Efficacy Scale, Notthingham Assessment Foot Care Behavior and 10gram monofilament test measurements. Demographic characteristics analysis using univariate tests, bivariate analysis with paired t-test and independent t-test. Results: There was a significant effect on the intervention group to increase self-efficacy p-value =0.011 (p< 0.005) and foot care behavior p-value =0.032 (p< 0.005). Based on the independent t-test, it was shown that the intervention had no effect on the increase in foot sensitivity p-value = 0.141 (p< 0.005). Recommendation: Educare diabetic education and exercise program has an effect on improving self-efficacy and foot care behavior. The Diabetic Educare education and training program is expected to be a modality in the preparation of foot care education and exercise programs as part of a holistic nursing intervention, in patients with type 2 diabetic mellitus. Keywords: type 2 diabetic mellitus; Self-efficacy;Foot care behavior; Sensitivity; Digital Application-Based Foot Care Education and Training Program